Lung immune incompetency after mild peritoneal sepsis and its partial restoration by type 1 interferon: a mouse model study - Qiuming Meng; Fumiko Seto; Tokie Totsu; Tomoyuki Miyashita; Songfei Wu; Masahiko Bougaki; Michiko Ushio; Takahiro Hiruma; Bruce C. Trapnell; Kanji Uchida (Intensive Care Medicine Experimental)
Abstract Background Sepsis is commonly associated with acute respiratory distress syndrome (ARDS). Although the exaggerated inflammation may damage intact lung tissues, a percentage of patients with ARDS are reportedly immunocompromised, with worse outcomes. Herein, using a murine sepsis model, time-course immune reprogramming after sepsis was evaluated to explore whether the host is immunocompromised. Leukocyte kinetics in the lung tissue were evaluated in a male C57/BL6 mouse model of mild peritoneal sepsis induced by cecal ligation and puncture, with the survival rate exceeds 90%. Lung immune reactivity was evaluated by intratracheal instillation of lipopolysaccharide (LPS; 30 µg). Furthermore, the effect of interferon (IFN)-β in vivo and ex vivo was evaluated. Results Four days after sepsis, the lung water content remained high, even among mice in clinical recovery. While monocytes and neutrophils gradually accumulated in the lung interstitium, the inflammatory cytokine/chemokine expression levels in the lungs continued to decline. Intratracheal LPS instillation induced more leukocyte trafficking and protein leakage into the alveoli in the septic lung, indicating more severe lung injury. However, LPS stimulation-associated mRNA expression of tnf, il6, ccl2, and cxcl1 was suppressed. Intra-alveolar expression of tumor necrosis factor (TNF)-α, interleukin (IL)-6, monocyte chemoattractant protein (MCP)-1, and keratinocyte-derived cytokine (KC) was also suppressed. Monocytes isolated from the lung tissue showed an impaired response in il6, ccl2, and cxcl1 to LPS. Systemic IFN-β restored the above impaired regulator function of monocytes, as did coculturing these cells from lung tissue with IFN-β. Conclusions Histologically accelerated inflammation and paradoxically suppressed immunological regulator signaling were observed in the early recovery phase of sepsis. This observation may provide a model for the immunologically irresponsive state that occurs in some patients with sepsis. Systemic IFN-β partly restored the post-septic immunocompromised state, indicating its therapeutic potential for the immunosuppressive state seen in some patients with sepsis/ARDS.